Nilai-Nilai Religius Dalam Peribahasa Madura - Rahmad, Rahmad; Supratman, Mohammad Tauhed; Rahman, Ainur; Hasanah, Nurul Luthfiatul; Miati, Miati (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2022)
The Madurese view of life cannot be separated from the religious values they profess. It is a fact that almost all Madurese are adherents of Islam. Their adherence to their religion is the identity of the Madurese that showed in their language and behavior. One form of language behavior is using Madurese proverbs with religious values. This study aims to determine the religious values contained in the proverbs of Madura. This study uses a qualitative method because the data is descriptive. In addition to analyzing the religious values contained in Madurese proverbs, this study also looks at the possibility of shifting the meaning of Madurese proverbs in the current era. The results of this study demonstrate three aspects of religious values: ideology, ritual worship, and religious experience. On the ideological side, there is a belief in the oneness of God as the absolute ruler in Madurese's life. The ritual aspect found worship behavior, especially the five daily prayers, that should not be abandoned. Aspects of religious experience are found in the presence of awareness and inner wealth in dealing with life's problems